A Social Ecological Framework: Counselors' Role in Improving Student Athletes' Help‐Seeking Behaviors. Issue 1 (6th April 2021) - Reich, Aviry L.; Milroy, Jeffrey J.; Wyrick, David L.; Hebard, Stephen P.
Abstract : Student athletes' demands increase their risk for experiencing mental health concerns (Ryan et al., 2018). Risk factors for student athletes include coping with athletic success and failure; balancing dual roles; dealing with identity confusion; and experiencing isolation, injury, career termination, and burnout (Beauchemin, 2012; G. T. Brown, 2014). Using the social ecological model, we review factors that interfere with student athletes' help‐seeking behaviors and propose recommendations for the ways counselors can address these barriers in the roles of educator, advocate, and therapist.